Assessment of Sensory Processing Characteristics in Children between 3 and 11 Years Old: A Systematic Review - Jorquera-Cabrera, Sara; Romero-Ayuso, Dulce; Rodriguez-Gil, Gemma; Triviño-Juárez, José-Matías (Frontiers in Pediatrics, 2017)
The assessment of sensory perception, discrimination, integration, modulation, praxis and other motor skills, such as posture, balance and bilateral motor coordination, is necessary to identify the sensory and motor factors influencing the development of personal autonomy. The aim of this work is to study the assessment tools currently available for identifying different patterns of sensory processing. There are fifteen tests available that have psychometric properties, primarily for the US population. Nine of them apply to children in preschool and up to grade 12. The assessment of sensory processing is a process that includes the use of standardized tests, administration of caregiver questionnaires, and clinical observations. The review of different studies using PRISMA criteria or Osteba Critical Appraisal Cards reveals that the most commonly used tools are the Sensory Integration and Praxis Test, the Sensory Processing Measure and the Sensory Profile.